Effectiveness and waning of protection with the BNT162b2 vaccine against the SARS-CoV-2 Delta variant in immunocompromised individuals - Szekanecz, Zoltán; Vokó, Zoltán; Surján, Orsolya; Rákóczi, Éva; Szamosi, Szilvia; Szűcs, Gabriella; Szekanecz, Éva; Müller, Cecília; Kiss, Zoltán (Frontiers in Immunology, 2023)
Introduction. In Hungary, the HUN-VE 3 study determined the comparative effectiveness of various vaccination strategies during the Delta COVID-19 wave. That study included more than 8 million 18-100-year-old individuals from the beginning of the pandemic. Immunocompromised (IC) individuals have increased risk for COVID-19 and disease course might be more severe in them. In this study, we estimated the risk of SARS-CoV-2 infection and COVID-19 related death in IC individuals compared to healthy ones and the effectiveness of the BNT162b2 vaccine. Patients and methods. Among the 8,087,988 individuals undergoing follow-up from the onset of the pandemic in the HUN-VE 3 cohort, we selected all the 263,116 patients with IC and 6,128,518 controls from the second wave, before vaccinations started. The IC state was defined as two occurrences of corresponding ICD-10 codes in outpatient or inpatient claims data since 1 January, 2013. The control group included patients without chronic diseases. The data about vaccination, SARS-CoV-2 infection and COVID-19 related death were obtained from the National Public Health Center (NPHC) during the Delta wave. Cases of SARS-CoV-2 infection were reported on a daily basis using a centralized system via the National Public Health Center (NPHC). Results. Out of the 263,116 IC patients 12,055 patients (4.58%) and out of the 6,128,518 healthy controls 202,163 (3.30%) acquired SARS-CoV-2 infection. Altogether 436 IC patients and 2141 healthy controls died in relation to COVID-19. The crude incidence rate ratio (IRR) of SARS-CoV-2 infection was 1.40 (95%CI: 1.37-1.42) comparing IC patients to healthy controls. The crude mortality rate ratio was 4.75 (95%CI: 4.28-5.27). With respect to SARS-CoV-2 infection, interestingly, the BNT162b2 vaccine was more effective in IC patients compared to controls. Primary vaccine effectiveness (VE) was higher in IC patients compared to controls and the booster restored VE after waning. VE regarding COVID-19 related death was less in IC patients compared to healthy individuals. Booster vaccination increased VE against COVID-19-related death in both IC patients and healthy controls. Conclusions. There is increased risk of SARS-CoV-2 infection and COVID-19 related mortality in IC patient. Moreover, booster vaccination using BNT162b2 might restore impaired VE in these individuals.